Barista's fracture: a new occupational hazard. Issue 5 (May 2020) - Yusuf, Baasil Syed; Segaren, Neil; Segaren, Nicholas; Di Mascio, Livio
Lesson: Stress fracture of the clavicle is a rare injury usually occurring in high-level athletes. It is typically a result of repetitive sporting activity or unusual strain. We present the first case of an occupational clavicle stress fracture in a young female barista. The patient initially presented with insidious onset clavicular pain. There was no history of trauma, and an undisplaced fracture was present on the plain radiograph but overlooked by the emergency physicians. Two weeks later, the patient presented again with worsening symptoms, and a displaced fracture of the clavicle was diagnosed on plain radiograph. A thorough occupational history revealed the cause of her pain, which was the mechanical activity of coffee tamping and the fracture went on to unite with no further complications. No other cause was found on investigations including magnetic resonance imaging. The fracture healed with cessation of coffee tamping. This case highlights a previously unrecognised occupational hazard of coffee tamping as a potential cause of stress fracture of clavicle.